The Quintessential PIC® Microcontroller - Katzen, Sid.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2005)
The Quintessential PIC® Microcontroller deals with the central `intelligence’ of most smart embedded digital systems and aims to give the reader the confidence to design, construct and program a real working system using the industrial standard and popular Microchip PIC family of devices as the exemplar. Aimed specifically at a readership with no prior knowledge of software, electronics or logic design, this book is suitable for both industrial engineers and hobbyists. Students of Electronic Engineering and Computer Science, taking relevant courses or engaged in project work at either an under- or postgraduate level, will find it an ideal textbook. The second edition has been extensively rewritten to both rationalize and clarify the introductory chapters and to update and extend the core material. Whilst the thrust remains with the Mid-range devices, an additional chapter has also been added on the Extended-range family. Key features include: • The use of current real-world hardware and software products to illustrate the material • Numerous fully worked examples as well as self-assessment questions • An associated web site providing solutions, further examples, listings and useful resources at http://www.engj.ulst.ac.uk/sidk/quintessential • Clear and concise presentation of key points and underlying concepts.
The Fundamentals -- Digital Representation -- Logic Circuitry -- Stored Program Processing -- The Software -- The PIC16F84 Microcontroller -- The Instruction Set -- Subroutines and Modules -- Interrupt Handling -- Assembly Language Code Building Tools -- High-Level Language -- The Outside World -- The Real World -- One Byte at a Time -- One Bit at a Time -- Time Is of the Essence -- Take the Rough with the Smooth -- To Have and to Hold -- Enhancing the Family -- A Case Study.
Keywords: Control engineering; Computer communication systems; Electronics; Microelectronics; Electrical engineering; Control and Systems Theory; Computer Communication Networks; Electronics and Microelectronics, Instrumentation; Communications Engineering, Networks